Proactive higher education for high technology. - Tadmor, Z. (IEEE spectrum)
Foreseeing a need for far more engineers and scientists than its universities were turning out, Israel's government, military, and academia worked in concert to entice students into technical fields. Appeals to patriotism were part of the mix. The national initiative clarified to high school graduates and young people who had done their military service the understanding that both their personal and the nation's future success lies in technology and science, and it urges everyone with the qualifications to study engineering and science. Special emphasis was placed on attracting women, who form Israel's largest untapped human resource in these fields. The national drive proved a resounding success. Today, enrollment in the Technion-Israel Institute of Technology in Haifa, the country's major and leading technological research university, is 40 percent higher than just two years ago. The other two engineering schools in the country, at the Tel-Aviv University and Ben Gurion University in Be'er Sheva, enjoyed similar surges in enrollment. At the same time, many colleges in Israel began educating students in disciplines pertaining to high-tech industries. In view of not one but two consecutive years of far greater enrollment nationwide, we would appear to have succeeded in reversing the decade-long decline in young people's interest in engineering and related studies